The Business of Certification - Scofield, Giles R. (The Hastings Center report, 2020)
The writer responds to the essay “Developing, Administering, and Scoring the Healthcare Ethics Consultant Certification Examination,” by Courtenay R. Bruce et al., in the September-October 2019 issue of the Hastings Center Report.